2018
DOI: 10.1123/jsep.2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

The Need-Relevant Instructor Behaviors Scale: Development and Initial Validation

Abstract: This article outlines the development and validation of the Need-Relevant Instructor Behaviors Scale (NIBS). Drawing from self-determination theory, the NIBS is the first observation tool designed to code the frequency and the intensity of autonomy-, competence-, and relatedness-relevant behaviors of exercise instructors. The scale also captures the frequency of need-indifferent behaviors. Methods: The behaviors of 27 exercise instructors were coded by trained raters on two occasions, before and after they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We will determine whether the intervention delivery style and content were as intended by coding audio recordings for need supportive strategies. 66 Specifically, this tool is designed to code the frequency and intensity of need supportive, indifferent and thwarting communication used by the coaches during session delivery. Audio recordings are used so that the coder can get a clearer indication of the qualities of delivery (eg, tone, sarcasm and so on), which are all important aspects of the motivational meaning of the communication style.…”
Section: Methods and Analysismentioning
confidence: 99%
“…We will determine whether the intervention delivery style and content were as intended by coding audio recordings for need supportive strategies. 66 Specifically, this tool is designed to code the frequency and intensity of need supportive, indifferent and thwarting communication used by the coaches during session delivery. Audio recordings are used so that the coder can get a clearer indication of the qualities of delivery (eg, tone, sarcasm and so on), which are all important aspects of the motivational meaning of the communication style.…”
Section: Methods and Analysismentioning
confidence: 99%
“…These authors argue that unresponsiveness or passive behavior from an individual's social environment could elicit autonomy indifference (i.e., a feeling of disinterest in the perspectives, preferences and opinions displayed by the person in authority), competence indifference (i.e., a feeling of unresponsiveness or negligence in creating conditions that will foster progress) and relatedness indifference (i.e., a feeling of apathy or inattentiveness from the person in authority). Quested et al (2018) made a case that need indifferent behaviors are empirically different from either active need-supportive or need-thwarting behaviors, and from exercisers' perceptions of passive behaviors. Quested et al (2018) asserted that they had "personally experienced and also observed exercise class instructors employing ongoing rhetoric throughout class that lacked qualities that would support or thwart autonomy, competence, or relatedness" (p. 261).…”
Section: Perceived Need-indifferent and Passive Behaviorsmentioning
confidence: 99%
“…Quested et al (2018) made a case that need indifferent behaviors are empirically different from either active need-supportive or need-thwarting behaviors, and from exercisers' perceptions of passive behaviors. Quested et al (2018) asserted that they had "personally experienced and also observed exercise class instructors employing ongoing rhetoric throughout class that lacked qualities that would support or thwart autonomy, competence, or relatedness" (p. 261). Bhavsar et al (2019) concluded that perceived need-indifference behaviors are also associated with needs frustration and, to a lesser extent, with perceived need-thwarting behaviors.…”
Section: Perceived Need-indifferent and Passive Behaviorsmentioning
confidence: 99%
“…In spite of the importance of developing relatedness-support strategies at the beginning (Ntoumanis et al, 2020) to create a strong group, given the breakdown in group cohesion caused by low attendance rates during the second academic year, it is of paramount importance to keep the relatedness-support strategies during the whole intervention. The intensity of relatedness-supportive behaviors of exercise instructors could be effective to overcome two of the major problems in this population (i.e., low attendance rates and high attrition; Craike et al, 2018; Quested et al, 2018). Moreover, the women also progressively perceived competence and autonomy support from their instructor during the intervention.…”
Section: Discussionmentioning
confidence: 99%